Church Planting in the Evangelical Revival a Cambridgeshire Baptist Perspective - Brown, Raymond Edward (Baptist quarterly, 2016)
The article traces the impact of the itinerant ministry of the Bedfordshire Anglican clergyman, John Berridge, on six Cambridgeshire villages, leading to the eventual establishment of Baptist churches in those communities. The process by which typical cottage meetings for new converts determined their denominational allegiance was often a lengthy process, and the choice frequently determined by the help generously given by nearby congregations and their Ministers. It notes the local opposition encountered in some contexts, the costly allegiance of early converts, and suggests some reasons for the popularity of their meetings, the form they may have taken and the literature that helped them.